SYSTEMATIK COMPARATIVE ANALYSIS OF THE MEANINGS OF ALL CONJUGATED TENSE FORMS OF THE RUSSIAN AND UZBEK VERB - Kurbanova Malika Khayitovna; Nazarova Lola Kurbanovna; Babaev Eldar Tofikovich (The Bioscan, 2026)
A comparative study of the grammar of two languages helps to better understand the common and specific features of both languages, helps to draw attention to those phenomena that remain unnoticed by researchers studying only one language. Uzbek and Russian languages are representatives of two different languages with different grammatical systems – Turkic and Slavic Keywords Comparative grammarverb in Uzbek and Russian, comparative grammar.